Batasan Tanggung Jawab Notaris dalam Mengonstatir Dokumen Pelengkap Akta Berupa Surat Kuasa yang Ditandatangani Secara Elektronik (Studi Kasus Notaris X di Jakarta Selatan) - Kirana, Bima Shazi Rajendra; Mohamad Fajri Mekka Putra (UNES Law Review, 2024)
In the practice of technology-based startup companies (start-ups), electronic signatures are often used, including in making power of attorney as a complementary document in making a deed, this does not rule out the possibility of human error in affixing an electronic signature, which can cause losses for the signatory. real hands. This research aims to determine the validity of the complementary document in the form of a power of attorney signed electronically by someone other than the account owner and the limits of the notary's responsibilities as a position that maintains the complementary document for the deed in the form of a power of attorney signed electronically. The doctrinal method with a case approach experienced by Notary X in South Jakarta was applied in this research. From the research results, it can be concluded that a power of attorney signed electronically by someone other than the electronic signature platform account holder is invalid, then the notary is only responsible for formal, not material, truth, so the notary is not responsible for the truth of an electronic signature made by Apart from the electronic signature platform account owner, there are tips from the resource person that can be put into practice in dealing with cases regarding electronic signatures.